Representation of Gus Dur's Message of Peace About Papua in Mamat Alkatiri's Stand Up Comedy - Lukman Hakim; Eka Anjani (Tribakti: Jurnal Pemikiran Keislaman, 2022)
The discussion of Papua conflict with all sorts of controversy has always captured the attention and sparked the response of many, ranging from the complexity of the underlying problem, international world intervention, gun contact to the lives of innocent civilians. Many people consider the best episode in the history of the Papua conflict resolution was when President Abdurahman Wahid (Gus Dur) took office. The research was intended to get an image of the representation of peace message that Gus Dur used in Mamat Alkatiri’s Stand Up Comedy on the Gusdurian First Friday Forum in Jakarta, which streamed on NU YouTube channel. The research used qualitative method of Roland Barthes’ semiotics model of analysis approach to produce comprehensive exposure. The research shows that Gus Dur’s peace message in Mamat Alkatiri’s stand up comedy suggests that Papua's conflict resolution was not carried out by violence and military operations. The thing to do is opening a dialogue room and promoting a humanist approach. In addition, Gus Dur also emphasized accommodations on local wisdom and cultural symbols as a reward for Papuanese identity. Despite raising controversy, however, over time, everything Gus Dur did turned out to be an idea to many that Papuan conflict solutions needed a particular approach.